Regression model and successive linearization approach to analyse stagnation point micropolar nanofluid flow over a stretching sheet in a porous medium with nonlinear thermal radiation. (20th August 2019) - Kumar, B; Seth, G S; Nandkeolyar, R
Abstract: The key objective of this paper is to examine the effect of second order slip on MHD mixed convective stagnation point flow of a micropolar nanofluid with thermal radiation, viscous and Joule dissipations, Brownian and thermophoretic diffusions, etc. The numerical solution of governing equations is obtained by the successive linearization method (SLM) (Motsa and Sibanda 2012 Comput. Math. Appl. 63 1197). A comparative study is performed between our outcomes and past acquired outcomes in a limiting sense. Numerous critical outcomes are uncovered in the present examination including in the presence of second order slip; first order slip shows the opposing tendency for fluid velocity and angular velocity, but in the absence of second order slip and the presence of mixed convection parameters it acts as an assisting parameter for fluid velocity and angular velocity. Regression analysis is used in many fields including industries, prediction and forecasting. Keeping this in mind, quadratic multiple regression analysis is performed for the skin friction coefficient and local Nusselt number. It demonstrates that when a free stream is moving with less velocity than stretching velocity, then a small variation in microrotation prompts substantial perturbation in skin friction in comparison to the mixed convection parameter. However, in the reverse case, the buoyancy force turns out to be more dominant.